Effects of green tea dust on the biochemical parameters, antioxidant capacity, and intestinal microbiota composition in goose - Gu, Zhuoya; Xu, Wenwu; Tian, Yong; Lu, Lizhi; Chen, Guohong (Frontiers in Veterinary Science, 2025)
IntroductionGreen tea dust (GTD), a by-product of tea processing, exhibits promising potential as a functional feed additive owing to its rich protein profile and bioactive compounds.MethodsThis study evaluated the impact of GTD inclusion on biochemical parameters, oxidative stress markers, intestinal morphology, and cecal microbiota in Zhedong White geese. A cohort of 120 21-day-old male geese was randomly allocated to four dietary regimens: a basal diet (CTRL) and basal diets supplemented with 10% (LGTD), 15% (MGTD), or 20% ET (HGTD). The experimental period lasted seven weeks.ResultsResults indicated that GTD supplementation exerted no significant influence on plasma lipid metabolism. However, graded GTD doses markedly elevated systemic antioxidant activity, as evidenced by improved plasma antioxidant indices. Morphometric analysis revealed enhanced intestinal absorptive function, characterized by increased villus height (VH), reduced crypt depth (CD), and elevated VH/CD ratios in the duodenum. Furthermore, GTD supplementation modulated cecal microbial communities, promoting a favorable microbiota profile.ConclusionThese findings underscore the utility of GTD as a dietary intervention to augment intestinal health and oxidative status in geese, providing empirical support for its broader adoption in poultry nutrition.